Analysis of the Inconsistency of The Constitutional Court’s Decision on Resolution of Regional Election Result Disputes - I Putu Gede Adhi Dananjaya; Sulaksono Sulaksono (NOVUM : JURNAL HUKUM, 2025)
The difference between election (Pemilu) and regional head election (Pilkada) systems stems from Constitutional Court decision No. 97/PUU-XI/2013. This decision states that the Constitutional Court does not have the authority to handle disputes over election results, unless a Specialized Judicial Body has not been established. However, the question is whether the Constitutional Court is still authorized to handle disputes over election results after Constitutional Court Decision Number 85/PUU-XX/2022, and whether there needs to be an adjustment regarding this authority in the 1945 Constitution. In this context, the understanding of the meaning of elections also needs to be studied after Constitutional Court Decision No. 85/PUU-XX/2022. Through a normative approach and by using primary and secondary legal sources, this study concludes that after Constitutional Court Decision No. 85/PUU-XX/2022, the distinction between the two regimes has disappeared, so that the Constitutional Court has the authority to permanently handle disputes over election results.